2020
DOI: 10.1038/s41590-020-00826-9
|View full text |Cite
|
Sign up to set email alerts
|

Distinct antibody responses to SARS-CoV-2 in children and adults across the COVID-19 clinical spectrum

Abstract: Clinical manifestations of COVID-19 caused by the new coronavirus SARS-CoV-2 are associated with age 1,2. Adults develop respiratory symptoms, which can progress to acute respiratory distress syndrome (ARDS) in the most severe form, while children are largely spared from respiratory illness but can develop a life-threatening multisystem inflammatory syndrome (MIS-C) 3-5. Here, we show distinct antibody responses in children and adults after SARS-CoV-2 infection. Adult COVID-19 cohorts had anti-spike (S) IgG, I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

63
491
16
10

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 448 publications
(599 citation statements)
references
References 52 publications
63
491
16
10
Order By: Relevance
“…Third, it was observed that children with COVID-19 have milder symptoms and better prognoses than adults (Ludvigsson, 2020), and age is a significant determinant in COVID-19 severity (Cummings et al, 2020;Yang et al, 2020;. Consistent with the above clinical manifestation, adult COVID-19 patients have higher titers of anti-SARS-CoV-2 antibodies than children (Pierce et al, 2020;Weisberg et al, 2020). Together, these features of antibody responses support the hypothesis that rapid and increased induction of antigen-specific IgG upon SARS-CoV-2 infection in adults may result in ADE and contribute to COVID-19 pathogenesis (Fierz and Walz, 2020) ( Figure 1B).…”
Section: Antibody-mediated Pathogenesis In Covid-19 Patientsmentioning
confidence: 79%
See 3 more Smart Citations
“…Third, it was observed that children with COVID-19 have milder symptoms and better prognoses than adults (Ludvigsson, 2020), and age is a significant determinant in COVID-19 severity (Cummings et al, 2020;Yang et al, 2020;. Consistent with the above clinical manifestation, adult COVID-19 patients have higher titers of anti-SARS-CoV-2 antibodies than children (Pierce et al, 2020;Weisberg et al, 2020). Together, these features of antibody responses support the hypothesis that rapid and increased induction of antigen-specific IgG upon SARS-CoV-2 infection in adults may result in ADE and contribute to COVID-19 pathogenesis (Fierz and Walz, 2020) ( Figure 1B).…”
Section: Antibody-mediated Pathogenesis In Covid-19 Patientsmentioning
confidence: 79%
“…COVID-19 positive adults developed anti-S IgG, IgM and IgA classes as well as anti-N IgG antibody, while COVID-19 positive children predominantly developed anti-S but not anti-N IgG antibody (Weisberg et al, 2020). Children had reduced breadth of antigen-specific antibodies as well as neutralizing activity, indicating a reduced humoral response (Pierce et al, 2020;Weisberg et al, 2020). These observations may be related to antibody-mediated disease pathology in adult patients.…”
Section: Humoral Responses To Sars-cov-2 Infection In Covid-19 Patientsmentioning
confidence: 90%
See 2 more Smart Citations
“…A recent study has characterised sex differences in the cytokine and cellular response, although identified no differences in anti-S1 IgG or -IgM between male and female cases [171]. With regard to age, recent data published beyond the cut off for this review has shown distinct antibody responses in children and adults, which may inform future understanding of the disease course in different age groups [172]. This is a welcome addition to the literature considering the lack of studies on children included identified for our review.…”
Section: Summary Of Findingsmentioning
confidence: 87%